2007
DOI: 10.1002/elps.200600772
|View full text |Cite
|
Sign up to set email alerts
|

Specific and genotypic identification of Cryptosporidium from a broad range of host species by nonisotopic SSCP analysis of nuclear ribosomal DNA

Abstract: The accurate identification of Cryptosporidium (Protozoa: Apicomplexa) species and genotypes is central to the understanding of the transmission and to the diagnosis and control of cryptosporidiosis. In this study, we demonstrate the effectiveness of nonisotopic SSCP analysis of a approximately 300 bp region of the small subunit (pSSU) of ribosomal DNA for the specific identification of and delineation among 18 different Cryptosporidium species and genotypes from a wide range of hosts. This mutation scanning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 53 publications
1
21
0
1
Order By: Relevance
“…Parasitol., 10 (4): 127-141, 2015 In accordance, during the present study, 823 bp fragments amplified from the 18S SSU rRNA gene could be noted after nested PCR reaction from buffalo's feces. Previous studies indicated the usefulness of the small subunit (SSU) ribosomal RNA genes as genetic markers for the specific identification of Cryptosporidium having relatively low intraspecific and relatively high interspecific sequence variation (Fayer et al, 2000;Xiao et al, 2004;Jex et al, 2007). Thus, they had been utilized in systematic (phylogenetic) investigations of Cryptosporidium providing the basis for the current classification of members within the genus (Morgan et al, 1999a;Xiao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Parasitol., 10 (4): 127-141, 2015 In accordance, during the present study, 823 bp fragments amplified from the 18S SSU rRNA gene could be noted after nested PCR reaction from buffalo's feces. Previous studies indicated the usefulness of the small subunit (SSU) ribosomal RNA genes as genetic markers for the specific identification of Cryptosporidium having relatively low intraspecific and relatively high interspecific sequence variation (Fayer et al, 2000;Xiao et al, 2004;Jex et al, 2007). Thus, they had been utilized in systematic (phylogenetic) investigations of Cryptosporidium providing the basis for the current classification of members within the genus (Morgan et al, 1999a;Xiao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular methods, particularly those based on the PCR, are being utilized increasingly, as they are often more sensitive and more specific than microscopic methods [39][40][41]. Employing genetic markers, such as the small ribosomal subunit (SSU or 18S) and second internal transcribed spacer (ITS-2) of nuclear ribosomal DNA, Cryptosporidium can be accurately identified to and differentiated at the species level [4,[42][43][44]. In addition, molecular methods using more ''variable'' markers allow the detection of population variants (called ''genotypes'' or ''subgenotypes'') within species, thus enabling an insight into the population genetics and epidemiology of cryptosporidiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated the utility of a nonisotopic SSCP approach for the delineation of 18 different species or genotypes of Cryptosporidium [12], a group of parasitic apicomplexans which commonly infects the gastrointestinal or respiratory tract of a wide range of vertebrates, including fish, amphibians, reptiles, birds and mammals, causing the disease cryptosporidiosis. Human cryptosporidiosis is of major importance globally [13], particularly in immuno-suppressed or -compromised individuals [13][14][15], and usually manifests itself clinically as watery, steatorrhoeic and/or foul-smelling diarrhoea.…”
Section: Introductionmentioning
confidence: 99%
“…Selecting genetic markers with sufficient levels of sequence variability within individual species of Cryptosporidium is critical for such investigations. Although a number of genetic loci (e.g., the small ribosomal subunit and the internal transcribed spacers of nuclear ribosomal RNA/DNA) provide the specific and/or genotypic identification of Cryptosporidium [4,12,31,33,34], the locus currently considered to hold most promise for population genetic investigations is the gp60 gene [3]. This gene encodes the 15 and 45 kDa glycoproteins (GP15 and GP45, respectively), proposed to be integral in sporozoite attachment during the penetration of the parasite into the intestinal host cells [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation